2012
DOI: 10.1002/pits.21619
|View full text |Cite
|
Sign up to set email alerts
|

Problematic students of NASP‐approved programs: An exploratory study of graduate student views

Abstract: This study reports the findings of an electronic exploratory survey of National Association of School Psychologists (NASP) Student Representatives. The purpose of the survey was to gather information about the perspective of graduate students concerning problematic peers and their experiences with them in school psychology training programs. Findings suggest that (a) students are unsure whether or not their training programs have an official procedure in place for dealing with problematic students; (b) the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The present charge to the profession is to reduce incidences of gateslipping (Gaubatz & Vera, ) that occur when questionable trainees are permitted to move on to the next gatekeeping checkpoint. Several authors (e.g., Gaubatz & Vera, ; Jacobs et al, ; Rosenberg, Getzelman, Arcinue, & Oren, ; Trimble, Stroebel, Krieg, & Rubenstein, ) found that student participants estimated the percentage of problematic peers in their training programs to be much higher than the estimates of faculty members. The top four observed problems were lack of awareness of impact on others, emotional problems, clinical deficiency, and poor interpersonal skills.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The present charge to the profession is to reduce incidences of gateslipping (Gaubatz & Vera, ) that occur when questionable trainees are permitted to move on to the next gatekeeping checkpoint. Several authors (e.g., Gaubatz & Vera, ; Jacobs et al, ; Rosenberg, Getzelman, Arcinue, & Oren, ; Trimble, Stroebel, Krieg, & Rubenstein, ) found that student participants estimated the percentage of problematic peers in their training programs to be much higher than the estimates of faculty members. The top four observed problems were lack of awareness of impact on others, emotional problems, clinical deficiency, and poor interpersonal skills.…”
mentioning
confidence: 99%
“…The current dilemma encountered by counselor educators and supervisors is that, beyond professional codes of ethics (e.g., ACA Code of Ethics ; ACA, ), there is not a set of standards for professional, interpersonal, and intrapersonal conduct expected of trainees that is commonly accepted within the clinical professions (Bodner, ; Henderson & Dufrene, ; Homrich, ; Jacobs et al, ; Trimble et al, ). ( Note .…”
mentioning
confidence: 99%
“…Additionally, programs that are American Psychological Association (APA) accredited and NASP approved may still be failing to properly train students in certain areas of competency, with 71% of graduates from accredited/approved programs reporting a perceived inadequacy of their program to provide sufficient training in behavioral evidence‐based interventions (Hicks, Shahidulla, Carlson, & Palejwala, ). Although it is the responsibility of school psychology programs and faculty to identify, and provide additional support to graduate students who may be lacking competency (Trimble, Stroebel, Krieg, & Rubenstein, ), it is often difficult for trainers to identify weaknesses as psychology trainees often showcase materials and cases that portray them in a positive light, and hide their weaknesses from their supervisors (Webb & Wheeler, ). Due to the increasing need for program accountability and difficulty gaining an accurate measure of students’ ability, new techniques for evaluating training program effectiveness and student competence are necessary.…”
Section: Self‐efficacy Is Associated With Learning and Academic Outcomesmentioning
confidence: 99%